2009
DOI: 10.1099/mic.0.022467-0
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical control of virginiamycin production in Streptomyces virginiae by three pathway-specific regulators: VmsS, VmsT and VmsR

Abstract: Two regulatory genes encoding a Streptomyces antibiotic regulatory protein (vmsS) and a response regulator (vmsT) of a bacterial two-component signal transduction system are present in the left-hand region of the biosynthetic gene cluster of the antibiotic virginiamycin, which is composed of virginiamycin M (VM) and virginiamycin S (VS), in Streptomyces virginiae. Disruption of vmsS abolished both VM and VS biosynthesis, with drastic alteration of the transcriptional profile for virginiamycin biosynthetic gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…S1A in the supplemental material). However, a closer look at the abundance of different regulator types and their function, which has been partially shown for virginiamycin regulation (15,16,56,57,58) but only deduced for GV/VG regulation (55), suggests that there exist different regulatory networks in all streptogramin producers (see Fig. S1B in the supplemental material): e.g., the virginiamycin cascade has no equivalent for PapR1 and PapR5 in abundance and function.…”
Section: Putative Interaction Partners Of Response Regulator Papr6mentioning
confidence: 99%
See 1 more Smart Citation
“…S1A in the supplemental material). However, a closer look at the abundance of different regulator types and their function, which has been partially shown for virginiamycin regulation (15,16,56,57,58) but only deduced for GV/VG regulation (55), suggests that there exist different regulatory networks in all streptogramin producers (see Fig. S1B in the supplemental material): e.g., the virginiamycin cascade has no equivalent for PapR1 and PapR5 in abundance and function.…”
Section: Putative Interaction Partners Of Response Regulator Papr6mentioning
confidence: 99%
“…The best-understood model for a targeted coordination of antibiotic biosynthesis is the A-factor regulatory cascade of Streptomyces griseus, which controls streptomycin biosynthesis (14). Further examples have been reported, e.g., for the regulation of the pristinamycin-related antibiotic virginiamycin of Streptomyces virginiae (15,16), tylosin production in Streptomyces fradiae (17), lankacidin/lankamycin biosynthesis in Streptomyces rochei (18), or auricin biosynthesis in Streptomyces aureofaciens (19).…”
mentioning
confidence: 99%
“…However, either papR6 inactivation or overexpression had almost no effect on PI (PIa) biosynthesis. These results clearly demonstrated that PapR6 functions as a pathway-specific activator of PII production in S. pristinaespiralis, resembling the function of its homolog VmsT from S. virginiae (22).…”
Section: Resultsmentioning
confidence: 56%
“…Hence, the role of VmsT in VM biosynthesis is likely indirect. It was suggested that VmsT may regulate the expression of another, unidentified gene(s) outside the VM biosynthetic gene cluster and then activate VM biosynthesis (22). Here we revealed that the role of PapR6 in PII biosynthesis is possibly exerted via directly controlling the transcription of the snaFE1E2GHIJK gene cluster.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation